Information about the direct beneficiaries of the different Mixed Farming Systems innovations in Bangladesh by 2024 - Haque, Abdul; Miajy, Abdullah; Debnath, Manik; Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2024)
Since 2022, the International Rice Research Institute (IRRI) has been carrying out the CGIAR research initiative on Mixed Farming Systems (MFS)in Bangladesh. From 2022, a total of 9234 farming households in 5 districts across northern and southern Bangladesh have benefited from various innovations as part of this initiative. This report provides information on 4942 households that were direct beneficiaries and participated in MFS activities in Bangladesh by 2024.